Vključevanje šolskih svetovalnih delavcev v različne oblike supervizije - Kovač, Jernej (Pedagoška obzorja, 2020)
Owing to the frequent work overload because of continuous contact and work with people, school counselors need various kinds of support. In recent years, supervision has become an increasingly common type of professional support. It helps the participants to reflect on their own work, identify the shortcomings and find new strategies for further work. To date, no studies have been carried out that would investigate the inclusion of school counselors in various forms of supervision. The aim of the article is to research the inclusion of school counselors in supervision. The study first and foremost wanted to determine in which types of supervision school counselors participate and potential differences depending on their education and the institution for which they work. The results showed that school counselors mostly participate in group supervision; in contrast, individual supervision is used the least. The study also showed that education and institutional background also have an influence on the form of supervision in which the counselors participate.
Keywords: group supervision; individual supervision; individualna supervizija; intervision; intervizija; school counselors; skupinska supervizija; šolski svetovalni delavci; team supervision; timska supervizija